Admicellar polymerization in a continuous stirred tank reactor for surface modification of silica : process optimization using commercial grade mixed surfactants - Nantaporn Pipithvittaya (Chulalongkorn University, 2014)
Thesis (M.Sc.) -- Chulalongkorn University, 2006